Impact of knowledge sharing on virtual team projects. (28th October 2019) - Seetharaman, A.; Saravanan, A.S.; Patwa, Nitin; Niranjan, Indu; Jadhav, Veena; Porkodi, V.P.
In recent studies, there has been much interest in sharing knowledge across virtual team projects, especially in the information technology (IT) industry. Virtual teams have become more prevalent in the IT industry, making use of varied culture, time zones and talents across the geography. This research examines the impact of knowledge sharing on virtual team projects - the relationship between impact of knowledge sharing and the factors influencing the same. The impact of knowledge sharing and the influencing factors are modelled, and the hypotheses are defined. These were tested with a sample of 241 respondents from IT and finance industry throughout the geography covering Asia Pacific, North and South America, Europe and the Middle East. Research findings indicate that the majority of the hypothesised paths are significant and accepted. Also, they indicate that the individual variables internal barriers, interpersonal conflicts, composition of team and skills required for the team members have a positive relation to knowledge sharing.